Digitalizing Tradition: State Power, Religious Authority, and the Reconfiguration of Pesantren Identity in Indonesia’s Society 5.0 Era - Siti Asmonah; Masdar Hilmy (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The digitalization of Islamic boarding schools (pesantren) has emerged as a significant policy agenda within Indonesia’s educational transformation toward Society 5.0. While digital technologies are widely promoted to enhance educational quality, governance efficiency, and digital literacy, their implementation within pesantren raises important questions regarding institutional autonomy, religious authority, and the preservation of Islamic educational identity. This study aims to analyze the politics of pesantren digitalization in Indonesia and examine how state-driven modernization agendas interact with the authority of kyai and the evolving identity of Islamic education. Employing a qualitative policy analysis design, the study utilizes document analysis of national regulations, policy reports, and scholarly publications related to pesantren, educational digitalization, and Islamic education. Data were analyzed through qualitative content analysis and thematic interpretation to identify recurring patterns, institutional responses, and policy implications. The findings reveal that digitalization functions not merely as a technological intervention but as a political and cultural process involving negotiation between governmental modernization objectives and the internal authority structures of pesantren. The study identifies four dominant institutional responses to digitalization (resistive, adaptive, progressive, and hybrid) each reflecting different configurations of leadership, organizational culture, and technological readiness. Furthermore, the kyai emerges as a pivotal actor who mediates technological change by legitimizing, regulating, and contextualizing digital innovation within Islamic educational values. The findings also indicate the emergence of a hybrid educational identity in which traditional religious learning coexists with digital literacy and modern institutional governance. This study contributes to the literature by conceptualizing pesantren digitalization as a process of political negotiation and identity reconstruction rather than a purely technological reform. The study further recommends participatory and context-sensitive digitalization policies that strengthen institutional capacity while preserving the distinctive cultural and religious foundations of pesantren.